Fabrication and evaluation of a portable and reproducible quartz crystal microbalance immunochip for label-free detection of β-lactoglobulin allergen in milk products - Mingfei Pan; Liping Hong; Jingying Yang; Xiaoqian Xie; Kaixin Liu; Shuo Wang (Food Science and Human Wellness)
In this study, a label-free, portable and reproducible immunochip based on quartz crystal microbalance (QCM) was developed for the qualitative detection of β-lactoglobulin (β-LG), an allergen, in milk products. Experimental parameters in the fabrication and regeneration procedure such as pH of the coupling microenvironment, amount of anti-β-LG antibody and regeneration reagent were optimized in detail. Under optimal conditions, the proposed QCM immunochip exhibited good recognition of β-LG, with a calibration curve of ΔF = 12.877Cβ-LG0.4809 (R2 = 0.9982) and limit of detection of 0.04 μg/mL. Additionally, this portable QCM immunochip had good stability, high specificity, and no obvious cross-reaction to three other milk proteins (α-casein, α-lactalbumin, and lactoferrin). It could compete a qualitative measurement within 5 min, and could be reused at least ten times. In the β-LG analysis of actual milk samples, the developed QCM immunochip yielded reliable and accurate results, which correlated strongly with those from the standard HPLC method (R2 = 0.9969). Thus, the portable, stable, and reproducible QCM immunochip developed in this study allowed the rapid, cost-effectively and sensitively measure the β-LG in milk products.